Distinct Life Histories Impact Dikaryotic Genome Evolution in the Rust Fungus Puccinia striiformis Causing Stripe Rust in Wheat. (9th April 2020) - Schwessinger, Benjamin; Chen, Yan-Jun; Tien, Richard; Vogt, Josef Korbinian; Sperschneider, Jana; Nagar, Ramawatar; McMullan, Mark; Sicheritz-Ponten, Thomas; Sørensen, Chris K; Hovmøller, Mogens Støvring; Rathjen, John P; Justesen, Annemarie Fejer
Abstract: Stripe rust of wheat, caused by the obligate biotrophic fungus Puccinia striiformis f.sp. tritici, is a major threat to wheat production worldwide with an estimated yearly loss of US $1 billion. The recent advances in long-read sequencing technologies and tailored-assembly algorithms enabled us to disentangle the two haploid genomes of Pst . This provides us with haplotype-specific information at a whole-genome level. Exploiting this novel information, we perform whole-genome comparative genomics of two P . striiformis f.sp . tritici isolates with contrasting life histories. We compare one isolate of the old European lineage (PstS0), which has been asexual for over 50 years, and a Warrior isolate (PstS7 lineage) from a novel incursion into Europe in 2011 from a sexual population in the Himalayan region. This comparison provides evidence that long-term asexual evolution leads to genome expansion, accumulation of transposable elements, and increased heterozygosity at the single nucleotide, structural, and allele levels. At the whole-genome level, candidate effectors are not compartmentalized and do not exhibit reduced levels of synteny. Yet we were able to identify two subsets of candidate effector populations. About 70% of candidate effectors are invariant between the two isolates, whereas 30% are hypervariable. The latter might be involved in host adaptation on wheat and explain the different phenotypes of the two isolates. Overall, this detailed comparative analysis of two haplotype-aware assemblies of P . striiformis f.sp . tritici is the first step in understanding the evolution of dikaryotic rust fungi at a whole-genome level.